Hispania, A journal devoted to the teaching of Spanish and Portuguese, published by the American Association of Teachers of Spanish and Portuguese, Los Angeles, University of Southern California, vol. 72, núm. 1, marzo de 1989. - Villarreal Vásquez, Luis José (Thesavrvs, 2023)
Reseña de revistas.